Report of the Ad hoc Group on the International Redfish Survey in the Norwegian Sea Revision 1 (AGRED) [16–18 September 2008 Revised January 2009 Copenhagen, Denmark] - ICES (ICES, 2008)
Contributors:Benjamin Planque